The behaviour of Au-Au wire bonds in extreme environments - Shepherd, D; Grant, P; Johnston, C; Riches, S (2010)
Microelectronics are being required to show high reliability within aero-engines, oil-gas wells and other extreme applications where devices can experience over 250°C, 1000bar, corrosive environments and significant vibration. Currently operation may be only possible for a small number of hours, which necessitates expensive shut-down and replacement. Wire bond interconnects continue to be critical to overall reliability though previous studies have shown that traditional Au-Al bonds fail in such environments due to microstructural instability. Au-Au bonds offer a potentially stable solution that is increasingly desirable as microelectronics are required to endure ever harsher conditions. Au ball bonds on two representative substrates with Au surfaces and ceramic bases have been exposed to 250 and 300°C in N 2 for up to 2000 hours. Substrate 1 was a high temperature co-fired ceramic (HTCC) with a Au coating above Ni-Co and W layers, and Substrate 2 was a Au thick film on alumina. Wire pull and ball shear tests for both sample types significantly exceeded industry specifications, though a decrease in yield strength was observed. Key samples were cross-sectioned and grain structure was revealed by ion channelling contrast within a focused ion beam (FIB) system. The yield strength decrease was attributed to the Hall-Petch effect through elimination of twin grains formed during bonding deformation. Electron probe microanalysis (EPMA) of underlying Ni showed little interdiffusion into the Au. Hence the mechanical robustness and microstructural stability of Au-Au wire bonds in extreme environments has been demonstrated and understanding of thermal ageing mechanisms has been improved.